Comparative Effectiveness of Analgesics to Reduce Acute Pain in the Prehospital Setting. (3rd March 2020) - Sobieraj, Diana M.; Martinez, Brandon K.; Miao, Benjamin; Cicero, Mark X.; Kamin, Richard A.; Hernandez, Adrian V.; Coleman, Craig I.; Baker, William L.
Abstract: Objectives : The objectives of this study were to assess comparative effectiveness and harms of opioid and nonopioid analgesics for the treatment of moderate to severe acute pain in the prehospital setting. Methods : We searched MEDLINE ®, Embase ®, and Cochrane Central from the earliest date through May 9, 2019. Two investigators screened abstracts, reviewed full-text files, abstracted data, and assessed study level risk of bias. We performed meta-analyses when appropriate. Conclusions were made with consideration of established clinically important differences and we graded each conclusion's strength of evidence (SOE). Results : We included 52 randomized controlled trials and 13 observational studies. Due to the absence or insufficiency of prehospital evidence we based conclusions for initial analgesia on indirect evidence from the emergency department setting. As initial analgesics, there is no evidence of a clinically important difference in the change of pain scores with opioids vs. ketamine administered primarily intravenously (IV) (low SOE), IV acetaminophen (APAP) (low SOE), or nonsteroidal anti-inflammatory drugs (NSAIDs) administered primarily IV (moderate SOE). The combined use of an opioid and ketamine, administered primarily IV, may reduce pain more than an opioid alone at 15 and 30 minutes (low SOE). Opioids may cause fewer adverse events than ketamine (low SOE) when primarily administered intranasally. Opioids cause less dizziness than ketamine (low SOE) but may increase the risk of respiratory depression compared with ketamine (low SOE), primarily administered IV. Opioids cause more dizziness (moderate SOE) and may cause more adverse events than APAP (low SOE), both administered IV, but there is no evidence of a clinically important difference in hypotension (low SOE). Opioids may cause more adverse events and more drowsiness than NSAIDs (low SOE), both administered primarily IV. Conclusions : As initial analgesia, opioids are no different than ketamine, APAP, and NSAIDs in reducing acute pain in the prehospital setting. Opioids may cause fewer total side effects than ketamine, but more than APAP or NSAIDs. Combining an opioid and ketamine may reduce acute pain more than an opioid alone but comparative harms are uncertain. When initial morphine is inadequate, giving ketamine may provide greater and quicker acute pain relief than giving additional morphine, although comparative harms are uncertain. Due to indirectness, strength of evidence is generally low, and future research in the prehospital setting is needed.